GRAPPA Acceleration Factors on Sagittal T2 Lumbar MRI Image Quality in Clinical Hernia Nucleus Pulposus - Pandoyo, Danu Alief; Fajarini, Eunike Serfina; Muhaimin, Muhaimin (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Hernia Nucleus Pulposus (HNP) is the most common cause of back pain in the elderly. The most sensitive imaging to see HNP is using MRI. MRI examinations that are a little long can cause patient discomfort, especially with clinical HNP, because patients will complain of pain located in the lower back and result in suboptimal MRI images, therefore requiring a relatively faster scan time, thus requiring the GRAPPA Parallel Imaging technique which can produce good image quality with a short scanning time. The purpose of this study was to compare the GRAPPA factor acceleration value and to determine the correlation between image quality and the use of different GRAPPA factor accelerations. This study used 10 samples of patients with clinical Hernia nucleus pulposus MRI T2 Sagittal FSE examination at Indriati Solo Baru Hospital using the GRAPPA Acceleration Factor value. The results of the GRAPPA technique images on each sample were assessed for image quality quantitatively based on the SNR value and scan time. Based on the SNR value results, Acceleration Factor 1 has a higher average value compared to Acceleration Factor 2 and 3, while Scantime Acceleration Factor 2 has a shorter scanning time compared to Acceleration Factor 1 and 3. The GRAPPA technique can be applied to produce good image quality with fast scanning time.